AL-'ALAQAH BAINA TAQSIM AL-SHAF AL-DIRASIY WA INJAZ AL-TALAMIDZ FI TA'LIM AL-LUGHAH AL-'ARABIYAH - Ridha, Muhammad; Albantani, Azkia Muharom (Arabi : Journal of Arabic Studies, 2016)
This research was aimed to identify the relation between classroom classification based on the cognitive level and students’ achievement in learning Arabic language. The method used in this research was quantitative using the samples all the 8th grade of MTsN 2 Jagakarsa, 50 students academic year 2012/2013. The research found that there was no relationship between classifying students based on their cognitive level and their achievement in Arabic language with the value (-0,130). This value is between (0,00 – 0,20) meaning that there is no correlation between those two variables. It means that the alternative hypothesis (Ha) was rejected and the null hypothesis (Ho) was accepted or there was no relationship between the variables.DOI: 10.24865/ajas.v1i2.14